Penerapan Cybercounseling Pada Konseling Individual Siswa Sekolah Menengah Kejuruan - Arizona Arizona; Nurlela Nurlela; Edi Harapan; Endang Surtiyoni; Putri Maulidina (Bulletin of Counseling and Psychotherapy, 2022)
The problem in this study between counseling teachers and students is that students are more interested in counseling through cybercounselling, counseling guidance teachers are easier to inform students through cybercounselling, students can be closer to counseling guidance teachers, students can also tell the problem more openly with counseling guidance teachers and make it easier for students to counsel remotely in addition to face-to-face counseling. This study aims to determine the application of cybercounseling in SMK PGRI 2 Palembang. The research method used is descriptive qualitative. Data collection techniques used were observation, interviews, and documentation. Sources of information in this study are counseling guidance teachers who apply cybercounseling, totaling 4 people and students totaling 3 people. The results showed that the implementation of cybercounseling at SMK PGRI 2 Palembang was running quite well, but it did not occur regularly because there was no specific schedule between the Guidance Counseling teachers and students at the time of implementation. The application of cybercounseling as a medium between Counseling Guidance teachers and students to assist students in solving problems and finding solutions to their problems.